(untitled) (Italian Journal of Public Health, 2011)
Background: Injuries are the major cause of death and disability in European children. This study explored socioeconomic and gender structures in association with nonfatal childhood injury rates by sex and age groups in Sweden. Methods: Six indicators of socioeconomic structure and three indicators of gender structure were combined using principal component analysis. Sex- and age-specific mean annual injury rates of fourteen Swedish municipalities were estimated (2000–2005). The associations were analysed with Pearson’s correlation coefficients. Results: Narrow gender ratio in unskilled occupations and in politics was positively associated with injuries in girls 6–17 years (r ≥ 0.7) and with fractures in boys 6–12 years of age (r = 0.5). Wider income distribution was negatively associated (r ≥ -0.4) with boys’ injuries and positively associated with fractures in girls 13–17 years (r = 0.5). Relative wealth and male manager dominance was negatively associated with injuries in children 0–5 years (r = -0.4). Relative poverty was not associated with nonfatal childhood injuries. Conclusions: The strength of the associations between socioeconomic and gender structures and nonfatal childhood injury rates varied by sex, age group and type of injury. Childhood injury preventive interventions should consider the local gender structure, area-level wealth and area-level income distribution, and not only area-level poverty.